PERAN PENGELOLAAN LINGKUNGAN DALAM PENCAPAIAN UMUR RENCANA JALAN - G. Gunawan (Jurnal Jalan-Jembatan, 2007)
General condition network of national roads in 2005 indicated 11% (3.809 Km), their condition were heavily damage, 8% (2.770 Km) light damage, about 81% (20.050 Km) in good condition. The increased damage of roads is caused by some factors: specification of construction is not appropriate and supervisor or implementer is not professional and nature disaster etc. But environmental factor often is forgotten. Studying of environment for building and increasing of roads based on Kepmen Lingkungan Hidup No. 17/2001 and Kepmen Kimpraswil No.17/2003 it’s clear, it must be equipped with AMDAL or UKL/UPL but the documents in realization are not benefit so that it is ignored and never to make survey too. Result of studying for some documents AMDAL or UKL/UPL inroads sector, damaged roads will not increase if the document are arranged professionally and responsibility, user has to do the suggestion in document. Technical studying of environment needs to the attention for increasing the roads plan age are tophographie data, soil data, social-economic survey, hydrology data (drainage system) and vegetation condition around the project area, including in environment control plan. That control on decrase road damage about 5-20%. Keywords : Environmental Control, Roads Contraction